2010
DOI: 10.1523/jneurosci.1619-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

In VivoDiffusion Tensor Imaging and Histopathology of the Fimbria-Fornix in Temporal Lobe Epilepsy

Abstract: While diffusion tensor imaging (DTI) has been extensively used to infer micro-structural characteristics of cerebral white matter in human conditions, correlations between human in vivo DTI and histology have not been performed. Temporal lobe epilepsy (TLE) patients with mesial temporal sclerosis (MTS) have abnormal DTI parameters of the fimbria-fornix (relative to TLE patients without MTS) which are presumed to represent differences in axonal/myelin integrity. Medically intractable TLE patients who undergo te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
168
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(189 citation statements)
references
References 36 publications
16
168
1
4
Order By: Relevance
“…It should be noted that despite the controversy over the interpretation of AD and RD measures (14), diffusion-imaging measures are sensitive to many tissue properties (33), including variation in myelin (34), axon diameter and packing density (35), axon permeability (33), and fiber geometry (36). Diffusion imaging can be adapted to generate axon diameter distributions (37) or estimates of myelin microstructure (38).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that despite the controversy over the interpretation of AD and RD measures (14), diffusion-imaging measures are sensitive to many tissue properties (33), including variation in myelin (34), axon diameter and packing density (35), axon permeability (33), and fiber geometry (36). Diffusion imaging can be adapted to generate axon diameter distributions (37) or estimates of myelin microstructure (38).…”
Section: Discussionmentioning
confidence: 99%
“…The use of such high-resolution MRI sequences noticeably facilitates the accurate identification of white matter bundles within the hypothalamus, which are subject to structural alteration in some disorders, and which are also key landmarks used in the planning of surgical approaches and electrode placement in patients. The fornix, which is composed of arch-shaped white matter fibers connecting the hippocampus to the mammillary body (Carpenter, 1985;Mark et al, 1993), has been suggested to play an important role in memory function (Tsivilis et al, 2008;Laxton et al, 2010) and has been shown to be morphologically altered in patients with temporal epilepsy (Supprian and Hofmann, 1997;Freeman et al, 2004;Concha et al, 2010). Its detailed examination is required for the surgical planning of transcallosal or transventricular tumor resection (Winkler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…for axonal packing (Concha et al, 2010). Animal studies show that neurobiological events affect the diffusion parameters differently.…”
Section: Effects Of Cognitive Demandmentioning
confidence: 99%